Calcaneal Plate for Medial Femoral Condyle Fractures—Is This It? A Clinical Case - Silva, Rómulo; Moreira, Elsa; Branco, Ricardo; Ferreira, Filomena; Areias, Margarida; Oliveira, Carolina; Alpoim, Bruno (The Surgery Journal, 2021)
Management of unicondylar femoral fractures is mainly done by open reduction and internal fixation. Anatomic reduction in the articular surface is paramount in this type of lesion. Medial condyle fractures lack specific osteosynthesis material for fixation.We report a case resolved with the sparsely documented technique using calcaneal plate fixation.
Keywords: knee; trauma; calcaneal; plate